Seed dormancy is modulated in recently evolved chlorsulfuron-resistant Turkish biotypes of wild mustard (Sinapis arvensis) - Topuz, Muhamet; Nemli, Yildiz; Fatima, Tahira; Mattoo, Autar K. (Frontiers in Chemistry, 2015)
Biotypes of the broad-leaved wild mustard (Sinapis arvensis L.) found in wheat fields of Aegean and Marmara region of Turkey were characterized and shown to have developed resistance to sulfonylurea (chlorsulfuron), an inhibitor of acetolactate synthase (ALS). DNA sequence analysis of the ALS genes from two such resistant (‘R’) biotypes, KNF-R1 and KNF-R2, revealed point mutations, CCT (Pro 197) to TCT (Ser 197) in KNF-R1 and CCT (Pro 197) to ACT (Thr 197) in KNF-R2; these substitutions are consistent with the presence of chlorsulfuron-insensitive ALS enzyme activity in the ‘R’ S. arvensis biotypes. An additional phenotype of chlorsulfuron resistance in the Turkish S. arvensis ‘R’ biotypes was revealed in the form of an altered seed dormancy behavior over 4 to 48 months of dry storage (after-ripening) compared to the susceptible (‘S’) biotypes. Seeds of the ‘S’ biotypes dry stored for 4 months had a higher initial germination, which sharply decreased with storage time, while the seeds of the ‘R’ biotypes had lower germination after 4-months storage, rising sharply and peaking thereafter by 24 months’ of dry storage. The ‘R’ biotype seeds continued to maintain a higher germination percentage even after 48 months of after-ripening. The seed weight of ‘R’ and ‘S’ biotypes after-ripened for 4 months was similar but those after-ripened for 48 months differed, ‘R’ seeds were significantly heavier than those of the ‘S’ seeds. Differential seed germinability between ‘S’ and ‘R’ biotypes was found not a case of differential viability, temperature regimen or non-response to pro-germination hormone GA3. These studies are of relevance to ecological fitness of herbicide-resistant biotypes in terms of seed viability and germination.